Kadar Karbohidrat Dan Kualitas Tepung Biji Gayam Pada Lama Perendaman Dan Metode Pengeringan Yang Berbeda - Zahiroh, Kholishotuz, Dra. Suparti, M.Si (2016)
Gayam (Inocarpus fagifer) has a carbohydrate and starch high. To get qualified flour the processing must be do well. The purpose of this research is to know the quality of gayam seed flour (color, aroma, texture) based on different of time soaking and drying method. And also carbohydrate level based on different of time soaking and drying methode. The method used in this study is an experimental method by using a completely randomized design (CRD) two factorial. The first factor is soaking time for 20, 40 and 60 minutes with the addition of sodium metabisulphite (Na2S2O5) 0.1%. The second factor is the drying method of drying sun for 3 days and oven for 2.5 hours at 70 ° C. The results of this study are the highest carbohydrate level on treatment N1P2 (20 minutes soaking and drying oven), which is 0,505 g / L (50.5%). Lowest carbohydrate level on N3P1 (soaking for 60 minutes and drying sunlight), which is 0,195 g / L (19.5%). The best quality gayam seed flour on N1P1 (20 minutes soaking and drying sunlight), which is a yellowish white color, slightly rough texture, little bit stingging smell